PREVENTION OF BREAST CANCER THROUGH PRIMARY HEALTH CARE TRAINING - Leite, Carlos Vinicius Pereira; Porsani, Mariana de Matos; Plácido, Marilda Vargas Freitas; Nunes, Daniel Rodrigues; Ferreira, Carla Leticia Carius (Mastology, 2019)
Introduction: The main barrier to the management of breast cancer cases in Brazil is mainly due to the long periods of time between the diagnosis of the patient and the beginning of treatment. Objective: To improve access to information, treatment and screening of cancer cases through the training of primary health care professionals. Methods: Two “booklets” containing information on breast cancer were created: one for the Community Health Agents (CHAs) and the other for the Primary Health Care Nurses and Doctors (PHCND). Two theoretical and practical training modules were also created: one for the CHAs and another for the PHCNDs. The theoretical module consisted of lectures about breast cancer, and in the practical module, doctors and nurses were inserted in the mastology outpatient service of the Alcides Carneiro Hospital. Results: Clinical procedures in 2016 (before training) and 2017 (after training) showed a 31% increase in mastologist consultations, 41% in the number of patients undergoing surgeries and 42% in breast surgeries. From 2016 to 2017 there was a 16.5% reduction in the incidence of breast cancer and the number of deaths remained stable. Conclusions: Primary health care training increased and qualified the early detection of breast cancer in the city of Petrópolis-RJ, optimized the population’s access to the specialized service and improved the quality of life of women with breast cancer. Primary health care training was effective, low cost and could be replicated in other Brazilian municipalities.